Populisme Islam Dalam Gerakan 212: Studi Kasus Pada Lima Organisasi Keagamaan - Dea Bhakti Pratama (Saskara : Indonesian Journal of Society Studies, 2021)
This study aims to describe the 212 movement as a phenomenon of Islamic populism based on socio-religious movements followed by various Islamic organizations and their contradictions with other Islamic organizations The results showed that the 212 movement phenomenon was followed by various religious groups, especially Islam, participation was based on various forms of motivation, demands, principles and organizational ideology. In addition, the research results show that not all Islamic organizations support the 212 movement, but there are contradictions among religious organizations regarding their perceptions of the 212 movement. Pros and cons tend to be based on interpretations of religious teachings as well as ideology and organizational principles. The results of the research are then analyzed using the concept of mass mobilization and Islamic populism in the study of social movements that lead to the populist movement. The research findings also show that there is a relationship between social movements and Islamic populism as evidenced by the finding of chains of equivalens and empty signifiers which have implications for the formation of political frointer in the Islamic populism movement 212.